Identification of the main mechanisms involved in the tolerance and bioremediation of Cr(VI) by Bacillus sp. SFC 500-1E - Ontañon, Ornella Mailén (2018)
Chromium pollution is a problem that affects different areas worldwide and, therefore, must be solved. Bioremediation is a promising alternative to treat environmental contamination, but finding bacterial strains able to tolerate and remove different contaminants is a major challenge, since most co-polluted sites contain mixtures of organic and inorganic substances. In the present work, Bacillus sp. SFC 500-1E, isolated from the bacterial consortium SFC 500-1 native to tannery sediments, showed tolerance to various concentrations of different phenolic compounds and heavy metals, such as Cr(VI). This strain was able to efficiently remove Cr(VI), even in the presence of phenol. The detection of the chrA gene suggested that Cr(VI) extrusion could be a mechanism that allowed this strain to tolerate the heavy metal. However, reduction through cytosolic NADH-dependent chromate reductases may be the main mechanism involved in the remediation. The information provided in this study about the mechanisms through which Bacillus sp. SFC 500-1E removes Cr(VI) should be taken into account for the future application of this strain as a possible candidate to remediate contaminated environments.